Information Systems and Technologies in Agronomy and Business: Employers-Oriented Study - Olena Kopishynska; Yurii Utkin; Viktor Lyashenko; Olha Barabolia; Olena Kalashnik; Svitlana Mororz; Olga Kartashova (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
This paper describes innovative approaches to the development of an academic course in information technologies in agronomy. The results of an effective combination of teaching methods through solving crosscutting situational tasks were created by a group of teachers. The authors demonstrate efficiency of introduction of modern information systems into the educational process due to the use of discipline software provided by stakeholders with the examples of interactive tasks in the environment of the IS for real-time production process management. Program results are corresponding to standards of higher education in Ukraine, to the European framework of e-competences and were discussed with employers, which are the heads of agricultural enterprises, representatives of agribusiness and IT companies. The article shows examples of motivational measures during training and summarizes the results of cooperation between universities and business. The relevance of the work is considering in the context of Agriculture 4.0's current trends and studying the needs of employers and software developers.